Variasi Bahasa Komentator Pertandingan Turnamen Agung Wilis Cup Banyuwangi - Lutfi Irawan Rahmat; Riska Fita Lestari (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
Language is a means of communication that is always used by humans in everyday life. Spoken language is closely related to situations, conditions, time and expressions of a person in speaking. The ability to speak is equally important in society. One of the speaking activities is to become a volleyball commentator. This research method is a qualitative research using a descriptive method. Descriptive research method is a type of research in which there is a factual description in exploring a phenomenon or event in the field. The data in this study are the style of language used by volleyball commentators as the subject of discussion. Based on research findings and discussion it can be concluded that. (1) The style of language used by the commentators for the Agung Wilis Cup volleyball tournament in Kabat District, Banyuwangi Regency has 3 different styles of language, namely repetition, metaphor and personification but with almost the same meaning but different meanings. (2) The style of language used by volleyball commentators at the Agung Wilis Cup volleyball tournament in Kabat District, Banyuwangi Regency. The language used in the ongoing volleyball match has a figurative meaning or has characteristics in the commentator's pronunciation, which can be in the form of enthusiasm or ridicule of volleyball players.